The impact of menstrual cycle phase and symptoms on sleep, recovery, and stress in elite female basketball athletes: a longitudinal study - Kullik, L.; Isenmann, E.; Schalla, J.; Kellmann, M.; Jakowski, S. (Frontiers in Physiology, 2025)
Aim: This study aimed to examine the influence of menstrual cycle phases and symptom burden on sleep quality and recovery-stress states in elite female basketball players.